Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1103/physrevb.74.241402
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of superconductivity and radial breathing modes in suspended ropes of carbon nanotubes by organic polymer coatings

Abstract: We have altered the superconductivity of a suspended rope of single walled carbon nanotubes, by coating it with organic polymers. Upon coating, the normal state resistance of the rope changes by less than 20 percent. But superconductivity, which on the bare rope shows up as a substantial resistance decrease below 300 mK, is gradualy suppressed. We correlate this to the suppression of radial breathing modes, measured with Raman Spectroscopy on suspended Single and Doublewalled carbon nanotubes. This points to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…15,16 Such conclusions apply however to pristine tubes since, e.g., coating of tubes by weakly bound ͑physisorbed͒ molecules was shown to quench the RBM mode. 17 In the present case of SiNWs, we can expect our results to be significantly altered upon functionalization by large molecules or coating by an all-around insulating gate.…”
mentioning
confidence: 89%
“…15,16 Such conclusions apply however to pristine tubes since, e.g., coating of tubes by weakly bound ͑physisorbed͒ molecules was shown to quench the RBM mode. 17 In the present case of SiNWs, we can expect our results to be significantly altered upon functionalization by large molecules or coating by an all-around insulating gate.…”
mentioning
confidence: 89%
“…To understand the link between the weakening of superconductivity and the effect of coating on the phonon modes of these ropes, we have investigated the effect of PMMA deposition on the Raman response of other suspended nanotubes [56]. We compared the relative intensity of the RBM with respect to the tangential modes (TM).…”
Section: Suspended Character Of the Tubesmentioning
confidence: 99%
“…[2][3][4] The nanotubes, which are nearly of the same diameter, can have different kind of helicities but in general 1 3 of them are metallic. 5,6 The transport properties of the rope is found to be strongly dependent on the amount of disorder within the tubes. 7,8 It has been reported that the intertube electronic transfer is enhanced in the presence of disorder, leading to a charge-carrier delocalization.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Later on, intrinsic superconductivity has been reported in ropes of CNT with a transition temperature T c = 0.55 K. 6,12,13 Ferrier et al 6 studied the dependence of the superconducting transition temperature on the number of the metallic tubes included in the rope and on the amount of disorder. They found that superconductivity arises only in ropes with more than 100 tubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation